Perceptions of patients and providers on the use of acupressure services at Public Health Centres, Tabanan District, Bali - I Made Sukawinaca; Komang Ayu Kartika Sari; I Made Ady Wirawan (Universitas Udayana, 2017)
Background and purpose: Acupressure services are available at some public health centres (PHCs) in Bali, but the service utilisation remains low. The purpose of this study is to explore the perception of patients and service providers on the use of acupressure services at PHC in Tabanan. Methods: This study used a qualitative design based on observation and in-depth interviews with 13 informants consisting of patients, health service practitioners, head of PHC and program manager at Tabanan Health Office. The informants were chosen purposively and the data were analysed thematically. Results: There were different perceptions regarding the benefits of acupressure services between patients utilising the services and those who had not. Patients who had undergone acupressure demonstrated positive perception of the service. Acupressure services are considered to be effective in dealing with patient complaints, have no side effects, and patients reported being satisfied with the services provided by the PHC. Patients who did not utilise acupressure services, view acupressure as an ineffective therapy with potential side effects that may endanger their health. These patients experienced trauma from similar massage techniques. Service providers lamented the absence of government support in the form of local regulations that would enable them to access funding, increase human resources and facilitate promotion of the services. Conclusions: Patient perceptions of acupressure services still vary, with some contraints in the implementation that consist of local regulation, operational fund and human resources. Acupressure services still require synergy between central and local government policies to support its implementation.